WAR AND HUMAN RIGHTS IN AFRICA: REFLECTIONS ON SEX RELATED ABUSES IN THE CONGOLESE, RWANDAN, LIBERIAN AND LIBYAN CONFLICTS - Osaro Edo, Victor; Adeyeri, James Olusegun (European Scientific Journal, ESJ, 2013)
A normal, entirely peaceful and conflict-free world though, ‘generally’ desirable, is indeed utopia. Through the ages it has become increasingly manifest that war and peace are two sides of a coin. Put bluntly, wars of different kinds and degrees are common elements in human societies. To be sure, war is an organized, armed and usually prolonged conflict between groups, states and some other parties characterized by huge aggression, social disruption and normally, high mortality. However, sex-related crimes especially against women have increasingly become a regular feature in theatres of war across the world, particularly in Africa. This paper is a historical reconstruction of the trajectory of war time sex-related human rights violations in Africa, using the Congolese, Rwandan, Liberian and Libyan conflicts as case studies. The study shall examine the nature and dimensions of such violations, as well as their implications for sustainable development.